A Koronivalu kei Bua: Hillforts in Bua Province (Fiji), their Chronology, Associations, and Potential Significance. (2nd October 2021) - Nunn, Patrick D.; Nakoro, Elia; Tokainavatu, Niko; McKeown, Michelle; Geraghty, Paul; Thomas, Frank R.; Martin, Piérick; Hourigan, Brandon; Kumar, Roselyn
Abstract: Sixteen hillforts constructed and occupied perhaps several centuries before contact in the early nineteenth century are described from Bua district in northern Fiji. These hillforts represent inland settlements in fortifiable locations on high volcanic islands, plausibly established in response to the outbreak of sustained conflict. The chronology and functions of these hillforts were investigated through mapping, excavation, and collection of oral traditions. Four groups of hillforts are recognized. The Seseleka and Yadua (Island) groups represent single polities, comprising a mountaintop site surrounded with fortified narrow steep-sided basalt ridges with tributary sites at lower levels functioning as lookouts and/or food-processing sites. The Northwest Bua group comprises mountaintop sites occupied only when aggressors threatened, and are otherwise characterized by occupation around their bases. The Inland Bua group ranges along one of the highest ridges in the area and were all reportedly in conflict with each other. The Buan hillforts represent those found elsewhere in Fiji and on other high Pacific Islands. Insights from the study of these hillforts illuminate this period of Fiji history and help interrogate broader questions about drivers and proximate causes of the conflict that may have seen hillforts established near simultaneously on high Pacific Islands during the last millennium.